Spatially truncated optical pumping cooling - J Gilbert; R Ferrier Wilson; J Roberts (New Journal of Physics, 2019)
We present both the theoretical description and experimental implementation of a novel cooling technique for ultracold atoms trapped in a confining potential. We call the technique ‘spatially truncated optical pumping cooling.’ By using the fact that the internal states of atoms can be manipulated by laser light focused on only part of a confined ultracold gas, high energy atoms can be preferentially selected and then slowed to achieve cooling without requiring the loss of any atoms. This technique uses cooling photons more efficiently on a per photon basis than Doppler or polarization gradient cooling, while having approximately the same degree of difficulty with regard to experimental implementation.